MGNREGA and Its Role in Rural Development: Examining the Impact of MGNREGA on Rural Economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
It is hard to think development of a any nation without the event of its rural economy, neglecting of rural development means neglecting of overall development of nation. the important development of India lies within the economic betterment of individuals lives in rural India that government must make strong economic policies and better implementing strategies. National Rural Employment Guarantee Act (NREGA) enacted by legislation of India on 25 August 2005 and it had been renamed because the Gandhi National Rural Employment Guarantee Act (MGNREGA) on 2nd October 2009 on the birth anniversary of Mahatma Ghandi. The act aims to get rid of the acute poverty and at making villages of country independent through productive assets creation. The Gandhi National Rural Employment Guarantee Act. (MGNREGA) was enacted in India with the varied multiple objectives of providing employment during a rights-based framework, addressing rural poverty, checking migration, and building rural infrastructure. As such, per annum around 15–20 percent of households in India overall and 30 percent in rural India receive some sort of employment share under the MGNREGA programme. MGNREGA enshrines the right of 1 hundred days of paid employment to any rural household, on employees demand. Though its scope is nationwide, there are wide inter-state also as inter district variations within the achievement of the objectives of the MGNREGA Act.